Financial Performance in Small and Medium-Sized Enterprises (SMEs): A Bibliometric Analysis of Scientific Production (2023)
SMEs play a leading role in the global economy, which is why their study is increasing attracting the interest of the scientific and academic community. This article explores the development of research in financial issues, which is one of the relevant aspects for the growth and competitiveness of this type of organizations. A scientific mapping of the research on financial performance and SMEs is carried out by tracking the scientific production registered in the Scopus and WoS databases. The most relevant regions, authors, institutions and journals are determined using bibliometric tools and techniques; the most representative documents of the area are also identified and classified using the metaphorical scheme of the tree. The results allowed to establish the seminal and structural works, as well as the sub-areas that emerge on the subject; the latter determine, in turn, the sub-areas or currents in which the research is framed. The most relevant country on this topic is Indonesia, followed by Australia and South Africa; the publication with the greatest impact is the UK Journal of Cleaner Production, and the most relevant author is Jain, Priyanka, from Delhi Technological University. Finally, an agenda for future research is proposed, including financial returns related to corporate social responsibility, business innovation and environmental sustainability.